Thermoluminescence analysis can identify irradiated ingredient in soy sauce before and after pasteurization. (May 2017) - Lee, Jeong-Eun; Sanyal, Bhaskar; Akram, Kashif; Jo, Yunhee; Baek, Ji-Yeong; Kwon, Joong-Ho
Abstract: Thermoluminescence (TL) analysis was conducted to identify small quantities (0.5%, 1%, and 1.5%) of γ ray-or electron beam-irradiated garlic powder in a soy sauce after commercial pasteurization. The sauce samples with γ ray- and electron beam-irradiated (0, 1 or 10 kGy) garlic powder showed detectable TL glow curves, characterized by radiation-induced maximum in the temperature range of 180–225 °C. The successful identification of soy sauces with an irradiation history was dependent on both the mixing ratio of the irradiated ingredient and the irradiation dose. Post-irradiation pasteurization (85 °C, 30 min) caused no considerable changes in TL glow shape or intensity. Interlaboratory tests demonstrated that the shape and intensity of the first TL glow curve (TL1) could be a better detection marker than a TL ratio (TL1/TL2). Highlights: Thermoluminescence (TL) characteristics were studied to identify irradiated ingredient in soy sauce. TL emission was found to be dependent on irradiation doses and blending ratios of the ingredients. TL technique was found to be successful in detecting irradiation status even after pasteurization. Inter-laboratory trial gave a clear verdict on irradiation detection potential of TL technique.